Substrate Inhibition in Ruthenium(III) Catalyzed Oxidation of Propane-1,3-diol by Periodate in Acidic Medium: A Kinetic Study - Koteswara Rao, K.V.S.; Nadh, R. Venkata; Ratnam, K. Venkata (Asian Journal of Chemistry, 2020)
Ruthenium(III) catalyzed oxidation of propane-1,3-diol by potassium periodate was studied in aqueous perchloric acid medium. Orders of reaction with respect to concentrations of oxidant, substrate, acid and catalyst were determined. First order in oxidant and catalyst concentrations, and inverse fractional order in acid medium were observed. In addition, substrate inhibition (i.e. a decrease in reaction rate with an increase in substrate concentration) was observed. Effect of addition of salt and solvent was studied. Based on the studies of temperature variation, Arrhenius parameters were calculated. Plausible mechanism was also proposed based on observed kinetics.